Answer:
1. k(x) = (3g + 5h)(x) = -24x+40
2. k(x) = (h - g)(x) = 0
3. k(x) = (g + h)(x) = -6x+10
4. k(x) = (5g + 3h)(x) = -24x+40
5. k(x) = (3h - 5g)(x) = 6x-10
6. k(x) = (5h - 3g)(x) = 10-6x
Explanation:
Given
h(x) = 5 - 3x
and
g(x) = -3 x + 5
1. k(x) = (3g + 5h)(x)
3*g(x) = 3(-3 x + 5)
=> -9x+15
5*h(x) = 5(5 - 3x)
=>25-15x
(3g + 5h)(x)=3*g(x)+5*h(x)
= -9x+15+25-15x
=-9x-15x+15+25
=-24x+40
2. k(x) = (h - g)(x)
(h - g)(x) = h(x) - g(x)
= 5 - 3x -(-3 x + 5)
=5-3x+3x-5
= 0
3. k(x) = (g + h)(x)
(g+h)x = g(x) + h(x)
= -3 x + 5 + 5 - 3x
= -6x+10
4. k(x) = (5g + 3h)(x)
5*g(x) = 5(-3 x + 5)
=-15x+25
3*h(x) = 3(5 - 3x)
=15-9x
(5g + 3h)(x) = 5*g(x) + 3*h(x)
= -15x+25+15-9x
= -15x-9x+25+15
=-24x+40
5. k(x) = (3h - 5g)(x)
(3h - 5g)(x) = 3*h(x)-5*g(x)
=15-9x-(-15x+25)
=15-9x+15x-25
=-9x+15x+15-25
=6x-10
6. k(x) = (5h - 3g)(x)
5*h(x)-3*g(x) = 25-15x - (-9x+15)
= 25-15x+9x-15
= 25-15-15x+9x
=10-6x